2019
DOI: 10.4103/jrpp.jrpp_18_85
|View full text |Cite
|
Sign up to set email alerts
|

Prescription pattern of antihypertensive drugs: An experience from a secondary care hospital in the United Arab Emirates

Abstract: Objective: The aim of the study was to examine the prescription pattern of antihypertensive drugs used in a secondary care hospital in the United Arab Emirates (UAE). Methods: It was a prospective, observational study carried out in 588 adult hypertensive patients presenting to medicine outpatient and inpatient departments of Dibba Hospital, Fujairah, UAE. The study was conducted for a period of 6 months from December 2017 to May 2018. Demographic and clinical data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…This is per a meta-analysis conducted by Anchala et al in 2014 [ 6 ]. The most common comorbidities in the study population were dyslipidemia, diabetes mellitus, cardiovascular diseases, and obesity, which is supported by the findings of the study by Alkaabi et al (2019) [ 15 ]. As per the literature, insulin resistance and obesity play a central role in causing HTN and dyslipidemia [ 16 ].…”
Section: Discussionsupporting
confidence: 82%
“…This is per a meta-analysis conducted by Anchala et al in 2014 [ 6 ]. The most common comorbidities in the study population were dyslipidemia, diabetes mellitus, cardiovascular diseases, and obesity, which is supported by the findings of the study by Alkaabi et al (2019) [ 15 ]. As per the literature, insulin resistance and obesity play a central role in causing HTN and dyslipidemia [ 16 ].…”
Section: Discussionsupporting
confidence: 82%
“…, 48. , 49 Other studies were conducted in Japan (n = 2), 25 , 26 Nigeria (n = 2), 14 , 15 Saudi Arabia (n = 2), 19 , 50 Egypt (n = 1), 22 Jordan (n = 1), 51 Pakistan (n = 1), 24 Bahrain (n = 1), 16 Kenya (n = 1), 27 Australia (n = 1), 34 Cyprus (n = 1), 35 Ireland (n = 1), 52 United Arab Emirates (n = 1), 18 Taiwan (n = 1), 53 and Mexico (n = 1). 17 …”
Section: Resultsmentioning
confidence: 99%
“… 15 , 16 , 19 , 24 , 25 , 30 , 34 , 35 , 38 , 45 , 52 Ten studies adopted a prospective study design. 18 , 20 , 23 , 28 , 29 , 32 , 40 , 41 , 46 , 48 Two studies were based on randomized controlled trials (RCTs) 21 , 43 and one study was qualitative using semi-structured interviews. 50 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the few single molecule drugs where WHO-DDD was not available, the most frequently sold strength was considered the DDD. Studies have shown that, with the exception of beta blockers, for all classes of antihypertensive drugs the prescribed daily dose (PDD) is consistently greater than DDD, and almost double for angiotensin converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARBs) [ 6 7 ]. Using the IQVIA data, the estimated number of patients on antihypertensive treatment were calculated based on a conservative prescription scenario of (PDD:DDD = 1.2) for single molecule drugs and (PDD:DDD = 1) for fixed-dose combinations (FDC) and the unmet need for treatment inferred.…”
mentioning
confidence: 99%